Mentors also need support: a study on their difficulties and resources in medical schools - Gonçalves, Marina de Castro Nascimento; Bellodi, Patricia Lacerda (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Mentors have been recognized as important elements in the personal and professional development of medical students. However, few investigations have sought to understand their development, needs and difficulties. Our objective was to investigate the perceptions of a group of mentors regarding difficulties experienced over time and the resources used to face up to them. DESIGN AND SETTING: Qualitative exploratory study on mentors at Faculdade de Medicina da Universidade de São Paulo (FMUSP). In the FMUSP Mentoring Program, mentors follow and guide students throughout the course, and are responsible for heterogeneous group of students, in relation to the academic year. METHOD: Semi-structured interviews were conducted with 14 FMUSP mentors. RESULTS: For many of the mentors, the difficulties related to initial doubts about the role, frustration with the students’ attendance and overloading of daily tasks. To address such difficulties, these mentors used external resources and their own life experience and personal way of dealing with situations. Some mentors did not perceive difficulties for themselves or for students. CONCLUSIONS: Like in other mentoring programs, many difficulties perceived by mentors seem to be derived from the context of medical education itself. However, unlike in other experiences, FMUSP mentors do not feel that there is lack of support for their role, since this is regularly provided in the structure and dynamics of the program. The “difficulty in perceiving difficulties”, presented by some mentors, demands further investigation for better and greater understanding.